Pengaruh Edukasi Perawat Terhadap Peran Orang Tua dan Tingkat Kecemasan Anak Pada Saat Pemasangan Infus di Ruang IGD RSUD Kajen - Ainia Dian Murniyanti; Heny Prasetyorini (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Intravenous (IV) insertion is an invasive medical procedure that frequently induces pain, fear, and anxiety in children. Parental presence plays a crucial role in providing emotional support and comfort. Nursing education is considered an effective strategy to enhance parents’ understanding and involvement, thereby helping to reduce children’s anxiety during medical procedures. This study aimed to examine the effect of nursing education on parental roles and children’s anxiety levels during IV insertion in the Emergency Department of RSUD Kajen. This study employed a quasi-experimental design using a posttest-only control group approach. The sample consisted of 46 pediatric patients and their parents, selected through accidental sampling. The intervention involved a single five-minute nursing education session. Research instruments included a structured educational plan (SAP), a parental role questionnaire, and the Pediatric Anxiety Rating Scale (PARS). Data were analyzed using the Mann–Whitney test. The results revealed that the majority of parents in the intervention group demonstrated good roles (91.3%), while those in the control group were predominantly in the moderate category (69.6%). Children in the intervention group mostly experienced mild anxiety (69.6%), whereas moderate anxiety was more common in the control group (52.2%). There was a statistically significant effect of nursing education on both parental roles and children’s anxiety levels (p-value = 0.001). Nursing education is therefore effective in improving parental involvement and reducing children’s anxiety during IV insertion.